The association between environmental factors and the development of Crohn's disease with focusing on passive smoking: A multicenter case-control study in Japan. - Kyoko Kondo; Satoko Ohfuji; Kenji Watanabe; Hirokazu Yamagami; Wakaba Fukushima; Kazuya Ito; Yasuo Suzuki; Yoshio Hirota; Japanese Case-Control Study Group for Crohn's disease (PLoS ONE, 2019)
Background The number of patients with Crohn's disease (CD) in Japan has recently been increasing. We examined the association between environmental factors and the development of CD in Japanese focusing on passive smoking. Methods We conducted a multicenter case-control study and compared the environmental factors of 93 cases who were newly diagnosed with CD to the environmental factors of 132 controls (hospital-, age-, and sex-matched patients with other diseases). The odds ratio (OR) of each factor for the development of CD and the 95% confidence interval (CI) were calculated using a logistic regression model. The association between the details of passive smoking history and the development of CD was examined for those who had an active smoking history "no". Odds ratios of number of passively smoked cigarettes (per day), time of passive smoking (per day) and period of passive smoking (year) were calculated using "passive smoking 'No'" as a reference. Results History of appendicitis, family history of inflammatory bowel disease, and active smoking history were not significantly associated with the development of CD. Drinking history showed a decreased OR for the development of CD (0.39, 0.19-0.77). "Passive smoking Yes" showed significantly increased OR (2.49, 1.09-5.73). Regarding the association between passive smoking and the development of CD, the OR increased as the number of cigarettes per day, smoking time per day, and smoking duration increased, and there was a dose-response relationship (trend P = 0.024, 0.032, 0.038). Conclusions The association between environmental factors and the development of CD among Japanese was examined by case-control study. It was suggested that the passive smoking history may be associated to the development of CD.